MODERN APPROACHES TO RISK MANAGEMENT IN INVESTMENT PORTFOLIOS: STRATEGIES IN MARKET VOLATILITY - Loso Judijanto; Yupiter Mendrofa; Iwan Harsono; Pirmanta Sebayang; Fuadah Johari (CV. Adiba Aisha Amira, 2025)
This paper explores the evolution of risk management strategies in investment portfolios, explicitly focusing on addressing challenges posed by market volatility. Effective risk management is paramount for safeguarding investor assets in an era of globalization, technological advancements, and heightened interconnectedness. Traditional theories, such as Modern Portfolio Theory (MPT) and the Capital Asset Pricing Model (CAPM), have provided foundational frameworks. However, limitations in addressing the dynamic nature of contemporary financial markets during periods of heightened volatility have led to the emergence of modern approaches. This study investigates the integration of technological advancements, insights from behavioral finance, and sophisticated quantitative models to provide nuanced and adaptive risk management strategies. Algorithmic trading, dynamic asset allocation models, and behavioral insights contribute to a comprehensive toolkit for managing risk during market volatility. The paper assesses the efficacy of these modern approaches in navigating the complexities of fluctuating markets and offers insights into the evolving landscape of risk management.